Sliding behavior of droplet on a hydrophobic surface with hydrophilic cavities: A simulation study - Yong, K.W.; Ganesan, Poo Balan; Kazi, Md Salim Newaz; Ramesh, Sathyadeepak; Badruddin, Irfan Anjum; Mubarak, Nabisab Mujawar (AIP Publishing, 2018)
This paper presents a detailed computational fluid dynamics simulation study on water droplet mobility and cavity fillings resulting from a sliding droplet on a titled surface or substrate with round shaped cavities in a serial arrangement. The effects of different hydrophobicity (or contact angle) values for cavity and non-cavity surfaces, cavity depths, cavity spacings, plate tilting angles, and initial droplet volumes on its mobility were investigated. The findings are reported in terms of the total number of filled cavities, its duration, and the average volume of droplet per cavity. This study can be useful for the design and development of the passive microfluidics related devices and applications.